2010
DOI: 10.1038/gt.2010.127
|View full text |Cite
|
Sign up to set email alerts
|

CD28 cosignalling does not affect the activation threshold in a chimeric antigen receptor-redirected T-cell attack

Abstract: Adoptive immunotherapy of cancer using chimeric antigen receptor (CAR)-engineered T cells with redirected specificity showed efficacy in recent trials. In preclinical models, 'second-generation' CARs with CD28 costimulatory domain in addition to CD3z performed superior in redirecting T-cell effector functions and survival. Whereas CD28 costimulation sustains physiological T-cell receptor (TCR)-CD3 activation of naïve T cells, the impact of CD28 cosignalling on the threshold of CAR-mediated activation of pre-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 34 publications
2
43
2
Order By: Relevance
“…1C). CAR-Ts can secrete IL2 when stimulated through their endogenous CD28 receptor (22) or the chimeric CD28-z receptor (19). Accordingly, we found that CAR-Ts engineered with 9-28-z but not z-CARs secreted IL2 (Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…1C). CAR-Ts can secrete IL2 when stimulated through their endogenous CD28 receptor (22) or the chimeric CD28-z receptor (19). Accordingly, we found that CAR-Ts engineered with 9-28-z but not z-CARs secreted IL2 (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Here, we first established that eradication of large established tumors can be achieved by HER2-specific CAR-Ts if provided with costimulatory CD28 signaling (28-z-CAR; ref. 19). This rejection was associated with sustained accumulation, proliferation, and differentiation of CAR-Ts to effector memory (TEM) cell type at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…The CARs used in this study are specific for Her2 and CEA and have been shown to eliminate tumor cells with the respective targets in a specific fashion (28,36). The Her2 and CEA are highly expressed in a variety of breast cancer and colorectal cancer (CRC) lesions, respectively (37,38), both of which have increased ROS production and local oxidative stress (15,39).…”
Section: Discussionmentioning
confidence: 99%
“…CAR-CAT were based on the CEA-specific CAR BW431/26scFv-IgG1-CD28-CD3z and the Her2-specific CAR C6-B1.D2-IgG1-CD28-CD3z (27,28) by inserting the full-length human catalase cDNA downstream of the internal ribosome entry site (Fig. 1A).…”
Section: Car-redirected T Cells Engineered With Catalasementioning
confidence: 99%
“…Next, second-generation CARs contain costimulatory signaling domains derived from T cell costimulatory, with receptors such as CD28 being the most common choice. CD28-mediated CAR signaling is preferred in inducing IL-2 secretion and promoting T cell amplification (Chmielewski et al, 2011). Besides CD28, other costimulatory molecules, such as tumor necrosis factor receptor superfamily member 9 (TNFRSF9, 4-1BB), tumor necrosis factor receptor superfamily, member 4 (TNFRSF9, OX40), inducible T-cell CO Stimulator (ICOS), and CD27, may be included in CAR construction to take advantage of their associated functions in regulating T cell proliferation, survival, and antitumor response.…”
Section: Introductionmentioning
confidence: 99%